Burgosko 1747ko dotrina: II. facsimilea eta hiztegia - Lakarra, Joseba Andoni (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1987)
This article sees the completion of our edition of the anonymous Basque translation of Astete which came out in Burgos in 1747. In ASJU XX-2 (1986), we reproduced the text, comparing it with Mendiburu's original and Larramendi's subsiguent revisions. Here, we present the facsimile and the dictionary of the translation. We believe that its vocabulary is of the greatest interest to those studying the history of Post-Larramendi lexicography. We dwell especially on the use of neologisms and reproduce the context in which each one appears, and do the same with words introduced by edo ("or").